Structure—longitudinal sound velocity relationships in glassy anorthite (CaAl2Si2O8) up to 20 GPa: An in situ Raman and Brillouin spectroscopy study - Moulton, Benjamin J.A.; Henderson, Grant S.; Martinet, Christine; Martinez, Valérie; Sonneville, Camille; de Ligny, Dominique (Geochimica Et Cosmochimica Acta, 2019)
Silicate glasses show widely varying changes in their longitudinal sound velocities below 10 GPa. These changes are often attributed to structural changes in the glass (or liquid) network. This study reports both sound velocities and structural analysis of CaAl2Si2O8 (anorthite) glass in situ up to 20 GPa, based on Brillouin and Raman spectroscopy results. In situ high-pressure Brillouin spectra of CaAl2Si2O8 glass were taken during two compression-decompression cycles. The second compression-decompression cycle up to 12 GPa displayed a perfectly elastic behavior indicating that 8% faster sound velocity arose from permanent densification during the first cycle. The longitudinal sound velocity was calculated from previously reported refractive index data and displayed distinct changes in behavior at 2 and 5 GPa. Anorthite (CaAl2Si2O8) glass displays an anomalous decrease in the longitudinal sound velocity up to ∼2 GPa. Above this pressure its longitudinal sound velocity is insensitive to pressure until 5 GPa and thereafter it displays a positive pressure dependence. The longitudinal sound velocity of CaAl2Si2O8 glass is quite distinct from both polymerized (e.g. silica, albite) and depolymerized (e.g. diopside) silicate glasses. Raman spectroscopy reveals that below 2 GPa there is a rapid decrease in the inter-tetrahedral angle within the aluminosilicate network. In fact, the sigma parameter, indicative of the overall intertetrahedral angle, displays three distinct pressure regimes comparable to the longitudinal sound velocity. The lowest pressure regime, <2 GPa, involves a wrinkling of four-membered tetrahedral rings as well as the formation of fivefold coordinated aluminum. Between 2 and 5 GPa, the closure in the inter-tetrahedral angle becomes weak and the Raman bands associated with the three- and four-membered tetrahedral rings are lost. Above 5 GPa, new contributions to the spectra indicate the presence of either fivefold silicon or sixfold aluminum. Comparison with silica and sodium aluminosilicate glasses leads to the suggestion that the sharp changes at 5 GPa may be attributed to the formation of highly coordinated silicon because aluminum coordination changes are thought to be continuous. The loss of the tetrahedral rings and the formation of highly coordination tetrahedral cations, such as Si or Al, could be accomplished if the tetrahedral cations form edge-sharing geometries. In contrast to known polymerized (e.g. silica, albite) and depolymerized (e.g. diopside, enstatite) silicate glasses, CaAl2Si2O8 glass displays a weak negative pressure dependence, as found in polymerized compositions, but a high overall longitudinal sound velocity, as found in depolymerized systems. These structure-property relationships suggest that fragility is a better measure of the high-pressure behavior of silicate glasses.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Aluminosilicate structure; Anorthite glass CaAl; Brillouin and Raman spectroscopy; Densification mechanisms; High pressure